Assessment of Placental Grading in Normal and Pregnancy Induced Hypertensive Mothers on Ultrasonography and Fetal Outcomes (Medical Forum Monthly, 2023)
Objective: To evaluate the placental grading on ultrasound to predict the fetal outcomes in pregnancy induced hypertensive mothers as well as normal mothers.Study Design: cross-sectional analytical studyPlace and Duration of Study: This study was conducted at the department of Obstetrics and Gynecology and Anatomy of Bahawal Victoria Hospital, Bahawalpur between December 2021 to September 2022.Materials and Methods: All the pregnant women with gestational age at least 28 weeks visiting the Obstetrics and Gynaecology Outpatient department during study duration were included in the study. Data was entered and analyzed through SPSS version 25. P value <0.05 was considered statistically significant.Results: The mean age of the study participants was 26.65±10.34 years. On ultrasound, 6.3% 25.9%, 35.4% and 32.4% were fell in placental Grade-0, Grade-I, Grade-II and Grade-III maturity respectively. There was found statistically significant relationship placental maturity and gestational age of normal and pregnancy induced hypertensive mothers. There was statistically significant association (p=0.001) between placental maturity of normal mothers and mothers with pregnancy induced hypertension (PIH). Results presented with early maturation of placenta among hypertensive mothers. When a woman has high blood pressure, her placenta matures sooner. It was hospital based cross sectional study in which women who were visiting the hospital were included hence it is very difficult to generalize these findings for general population.Conclusion: Ultrasonography predicted excellent picture for diagnosis of Grade-III placenta and it is more safe method than invasive procedures like amniocentesis.